Letter (copy) : Spanish Refugee Children - Tewson, Vincent
1939-10-30 038-0062-001 Secretary's. HVT/FC/EK/241. 30th October, 1939. Mr. A. Hooper, Mansfield and District Trades Council, Salisbury House, Salisbury Road, MANSFIELD. Dear Mr. Hooper, SPANISH REFUGEE CHILDREN. Referring to your letter of the 28th October, the number of children who originally came to this country was in the neighbourhood of four thousand. Three thousand have already been returned and of the thousand remaining it is likely that between four hundred and five hundred will be returned to Spain as soon as the necessary transport facilities can be secured. The Committee responsible for the care of these children is the National Committee for the Care of Basque Children, upon which the General Council are represented and of which I happen to be the Vice-Chairman. In certain cases the financial responsibility for a Home is taken by a Local Committee in the district, but in many instances the National Committee is compelled either to be entirely or partly responsible for maintenance. I could not say with certainty whether there is any evacuated area in which Basque children 292/946/38/62(I)